Efectos Que Genera La Disfuncionalidad Familiar En El Rendimiento Académico De Los Estudiantes De La Unidad Educativa Ernesto Velásquez Kuffo Del Cantón Pichincha, Provincia De Manabí. - Zambrano Zabala, Winter Robinson (2014)
Family dysfunctionality in the academic performance of students conducted the study on the effects generated is in the Velasquez Kuffo Ernesto educational unit, located in the canton of Pichincha, in the province of Manabi, which took a representative sample of students, teachers and parents to implement the field study and through this achieve the goals. The present study determined the effects generated by family dysfunction in performance academic students of the educational unit, in the same way he identified the types of family dysfunctionality facing learners and checked how these bear family dysfunctionality in their home study and to the inside of the educational unit, so surveys were implemented to the educational communityin order to collect information regarding the variables of the object of study and at the same time check the hypothesis of the research. According to the results achieved through the field survey, identified several types of family dysfunctionality faced by students of the educational unit Ernesto Velasquez Kuffo of the canton of Pichincha, among them; psychological disorders, anxiety and depression before the economic situation that traverse households, product of unemployment; alcoholism and family abuse are other factors which generate dysfunction, this is compounded by the absence of parents, who are not interested in the integral formation of their children and what happens in their daily lives. The results lead to the design and implementation of programmes to inform parents about the need to give their children a safe, stable and without conflicts, family environment since if it does not, they will be affected seriously in their academic performance, as well as in their personal relationships. From the study is defined as the scope of the proposal, the need to improve relations between parents and children, thus positively influencing student performance of learners.